INFLUENCE OF AQUEOUS EXTRACT OF BARLEY SPROUTS, TREHALOSE, AND CALCIUM ON GROWTH, QUALTY AND YEILD OF CARROT - Al-Khafaji, Aseel M. H. H.; Al-jubouri, Kadhim D. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This research was implemented at vegetable field of the College of Agricultural Engineering Sciences - University of Baghdad during fall seasons, 2018 and 2019. The experiment was conducted using factorial within Randomized Complete Block Design arrangement with three factors and replicates (3X3X2). The aqueous barley sprouts extract (B0, B1) (0, 100 g.L-1) represented the first factor. Trehalose (T0, T1, T2) (0, 50, 75 mmole.L-1) represented the second factor. Calcium (C0, C1, C2) (0, 1, 2 ml.L-1) represented the third factor. The research objectives are assessing the impact of the mentioned factors and their interaction on carrot vegetative, quality, and yield traits. Results showed the effectiveness of three ways interaction treatment B1T2C1 in producing significant increases in leaves number (14, 13, total sugars in roots (8.619, 8.15mg.100-1g) and carrot weight (161.6, 159g) for both seasons respectively.in compare with control treatment B0T0C0.